Comparing the effect of arbuscular mycorrhizal fungi on upland rice and macaranga denticulata in soil with different levels of acidity - Somchit Youpensuk (2018)
Macaranga denticulata Muell, Arg. is a fallow-enriching tree in upland rice fields where rotational shifting cultivation is practical. It was found associated with high diversity of arbuscular mycorrhizal (AM) fungi in the village of Haui Tee Cha, Sob Moei District, Mae Hong Son Province of northern Thailand. Soils in the village had low available P (about 2-4 mg/kg by Bray II), and pH ranging from about 4.5 to 6.0. This study evaluated the effects of AM fungi on upland rice in comparison with M. denticulata and root colonization in the host plants in three levels of soil pH, 4.5, 5.9 and 7.8, in a pot experiment. The optimal soil pH for growth of upland rice and M. denticulata were 4.5 and 5.9, respectively. In spite of almost no difference in the percentage root colonization and spore density, the effect of AM on growth of upland rice was very different from that on M. denticulata. AM fungi had no effect on dry weight and grain yield of upland rice. But in M. denticulata, AM fungi increased dry weight and nutrient contents, especially at pH 4.5 and 7.8. However, AM fungi significantly increased the nutrient content in seeds of upland rice in pH 7.8 soil. These results indicate that AM fungi play an important role in the maintenance of soil fertility and upland rice productivity in shifting cultivation by enhancing accumulation of nutrients in the fallow enriching M. denticulata.